The place of human in the changes of the political theology of Christianity Focusing on the holy text - elnaz parvanehzad; Abolfazl Shakoori (رهیافتهای سیاسی و بین المللی)
divine philosophers and thinkers believe that the Hebrew tradition and the rational system of ancient Greece had an ontological influence on Christian theology and its sacred text. . Given this as a fact, this paper aims to answer the question “how Christian theology led to the creation of humanism, especially in the modern political theories?” During the research, we realized that the dialectical transition of the West from medieval church dominance to the subjectivity of man cannot be considered a paradigmatic shift. Rather, the Christian doctrine of Trinity extends the embodiment of the “Spirit of God” in the “Son of God” to the pragmatism in the Son of Man (Jesus Christ), and justifies it through the Hebrew tradition and the ancient Greek philosophy. Using comparative-interpretive method, this research tries to find the reasons why Christian political theology shifted from “asceticism” in early Christianity to the subjugation of man by the church, and later on, what happened in dark medieval times is discussed and that how Christian political theology had to accepted “humanism” and “rationality” inevitably to cope with the modern times.